Chronic Lung Diseases and Depressive Symptoms in Older Adults: Insights from Observational Studies and Mendelian Randomization - Liu H; Yao Y; Yang Y; Wang J; Yu J; Xu X; Luo X; Zhang Y; Song X (Journal of Multidisciplinary Healthcare)
Huifang Liu,1– 5,* Yisong Yao,2– 5,* Yujuan Yang,2– 5,* Jianwei Wang,2– 5 Jingyi Yu,2– 5 Xinjun Xu,2– 5 Xianghuang Luo,2– 6 Yu Zhang,2– 5 Xicheng Song2– 5 1Second Clinical Medicine College, Binzhou Medical University, Yantai, People’s Republic of China; 2Department of Otorhinolaryngology, Head and Neck Surgery, Yantai Yuhuangding Hospital, Qingdao University, Yantai, People’s Republic of China; 3Shandong Provincial Key Laboratory of Neuroimmune Interaction and Regulation, Yantai, People’s Republic of China; 4Shandong Provincial Clinical Research Center for Otorhinolaryngologic Diseases, Yantai, People’s Republic of China; 5Yantai Key Laboratory of Otorhinolaryngologic Diseases, Yantai, People’s Republic of China; 6School of Clinical Medicine, Weifang Medical University, Weifang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xicheng Song, Department of Otolaryngology, Head and Neck Surgery, Yantai Yuhuangding Hospital, Qingdao University, Yantai, 264000, People’s Republic of China, Tel +865356691999, Fax +865356240341, Email drxchsong@163.com Yu Zhang, Department of Otolaryngology, Head and Neck Surgery, Yantai Yuhuangding Hospital, Qingdao University, Yantai, 264000, People’s Republic of China, Email superzhang013@163.comIntroduction: To elucidate the currently unknown relationship between chronic lung diseases (CLDs) and depressive symptoms among older adults.Methods: A total of 8079 older adults from China Longitudinal Aging Social Survey (CLASS) and 1119 individuals from a Sichuan Province cohort were included in this study. We used regression analysis and propensity score matching (PSM) to assess the association between CLDs and depressive symptoms among older adults, while the causal relationship was assessed using Mendelian randomization (MR). Our sensitivity analyses included heterogeneity tests, tests of multiple validity, and leave-one-out tests. A two-way mediation analysis was also used to assess the mediating role of basic activities of daily living (BADL) between CLDs and depressive symptoms.Results: In this cross-sectional study, we found that depressive symptoms significantly (P < 0.001) increased the risk of CLDs (β = 0.047). The robustness test showed that there were significant association between CLDs and depressive symptoms (β = 0.220, P < 0.001), Qi depression constitution (β = 8.564, P < 0.001). This finding was also confirmed through robustness tests using different PSM methods. The results of the inverse-variance weighting (IVW) analysis showed that depression increased the risk of idiopathic pulmonary fibrosis and asthma, with Beta coefficients of 2.822 [standard error (SE) = 1.087; P = 0.009] and − 1.090 (SE = 0.491; P = 0.027), accordingly. The results of the IVW analysis showed that idiopathic pulmonary fibrosis and asthma increased the risk of depression, with Beta coefficients of 2.822 [standard error (SE) = 1.087; P = 0.009] and − 1.559 (SE = 0.633; P = 0.013). The sensitivity analysis results confirmed the reliability of this conclusion. The mediating role of BADL was observed from depressive symptoms to CLDs.Conclusion: Depressive symptoms are associated with an increased risk of CLDs, reduced BADL promote the risk of CLDs in older adults with depressive symptoms, but the underlying pathological mechanism still needs to be clarified in future research.Keywords: cross-sectional study, propensity score matching, Mendelian randomization, chronic lung diseases, depressive symptoms